2014
DOI: 10.1371/journal.pone.0116186
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Loss of Lumbar Spinal Lordosis and Mobility – A Study of 323 Asymptomatic Volunteers

Abstract: BackgroundThe understanding of the individual shape and mobility of the lumbar spine are key factors for the prevention and treatment of low back pain. The influence of age and sex on the total lumbar lordosis and the range of motion as well as on different lumbar sub-regions (lower, middle and upper lordosis) in asymptomatic subjects still merits discussion, since it is essential for patient-specific treatment and evidence-based distinction between painful degenerative pathologies and asymptomatic aging.Metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 50 publications
1
21
4
Order By: Relevance
“…; Dreischarf et al. ), but determining how sex affects flexion and extension separately at the intervertebral level may provide insight into how vertebral wedging impacts intervertebral motion and whether females have a greater range of lumbar spine extension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Dreischarf et al. ), but determining how sex affects flexion and extension separately at the intervertebral level may provide insight into how vertebral wedging impacts intervertebral motion and whether females have a greater range of lumbar spine extension.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will be directed to understanding sex-differences in the sagittal range of motion of the lumbar spine. Prior work has shown that there are sex-differences in sagittal range of motion of the lumbar spine (Burton & Tillotson, 1988;Sullivan et al 1994;Dreischarf et al 2014), but determining how sex affects flexion and extension separately at the intervertebral level may provide insight into how vertebral wedging impacts intervertebral motion and whether females have a greater range of lumbar spine extension.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports regarding the decrease in LL in elderly populations. One paper mentioned that LL tended to decrease after 60 years of age 22 , and another paper stated that LL decreased after forty to fifty years of age 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Beside these factors, and others related to the variability of the lumbar spine as subject of study—number of vertebrae used, pathological or nonpathological spines, presence or absence of lumbosacral transitional vertebrae, presence or absence of scoliosis, and so forth, discrepancies found among studies of sexual dimorphism and population variation could also stem from differences in the inclusion/exclusion criteria used by each author, which are often based on the sample's age range. Some consider age‐related degeneration to have an influence on the lumbar curvature—either increasing it (Jentzsch et al, ) or decreasing it (Dreischarf et al, ; Gelb, Lenke, Bridwell, Blanke, & McEnery, ; Korovessis et al, ; Merrill et al, ; Pries et al, )—and prefer to choose a younger‐aged sample in order to eliminate its effect in studies where age variation is not the main subject of study (Bailey et al, ). On the contrary, other authors do not find any relation between lordosis and age (Kalichman et al, ), and thus do not make any exclusions regarding age.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the degree of lumbar lordosis varies greatly throughout an individual's life history—during postnatal ontogeny, the lumbar lordosis is established and reaches its initial adult configuration shortly after puberty (Reichmann & Lewin, ; Shefi et al, ). During adulthood, the lumbar lordosis can change further with the senescence process (Dreischarf et al, ; Jentzsch, Geiger, König, & Werner, ; Korovessis, Stamatakis, & Baikousis, ; Pries, Dreischarf, Bashkuev, Putzier, & Schmidt, ). These changes are closely related to factors such as bone and soft tissue degeneration (Bogduk, ), genetic make‐up variability in different populations (i.e., inter‐population variation) and sexual dimorphism.…”
Section: Introductionmentioning
confidence: 99%